Bridging Mathematics Literacy and Technology: A Self-Regulated Problem-Based Learning Approach - Kusuma, Dani; Sukestiyarno, Y L (Journal of Innovation and Research in Primary Education, 2025)
The mathematical literacy of Indonesian students is still low since mathematical literacy is one of the capacities that every individual must possess to be competitive in this era by being able to formulate, implement, and interpret mathematics in various contexts of life. This study aims to develop a learning model to improve students' mathematical literacy. The model developed is Self-Regulated Problem-Based Learning (SRPS). The type of research used is development research (RnD) using the Analysis, Design, Development, Implementation and Evaluation (ADDIE) model. The research subjects were 15-year-old 8th-grade junior high school students. The research findings show that the SRPS model of learning has a learning syntax that requires students to follow a systematic learning process. The applied learning syntax begins with problem presentation, analysis, planning, prioritizing, decision-making, discussion, and evaluation. The syntax of SRPS learning integrates problem-based learning and executive function, resulting in a sequence of learning processes that train students to understand problems, plan, make decisions, and evaluate the solutions they design. Learning syntax is integrated into the digital learning system to systematize learning processes and develop learning habits. The final achievement of the research shows that the development model produced meets the criteria of valid, effective, and practical.